Planar heterojunctions for reduced non-radiative open-circuit voltage loss and enhanced stability of organic solar cells. Issue 35 (17th May 2021) - Li, Yawen; Lin, Yuze
Abstract : Planar heterojunction organic solar cells exhibit lower trap density, higher electroluminescence efficiency, smaller non-radiative open-circuit voltage loss and better stability than bulk heterojunction counterparts. Abstract : Compared to bulk heterojunctions (BHJs) in organic solar cells (OSCs), planar heterojunctions (PHJs) avoid complicated morphology control entirely and morphology disorder caused by physical blending, and show huge potentials to realize less traps and better stability for OSCs. In this study, solution-processed fused-ring electron acceptors, replacing traditional fullerene acceptors such as C60 and C70, with several vacuum-deposited donors were employed to fabricate PHJ-OSCs. PHJ-OSCs exhibit a much lower trap density of 10 15 cm −3 magnitude than that of BHJ counterpart devices (10 16 cm −3 magnitude). Furthermore, PHJ-OSCs achieved the highest electroluminescence efficiency of 5.8 × 10 −3 and the smallest non-radiative open-circuit voltage loss of 0.13 V in the field of OSCs to date. Meanwhile, PHJ-OSCs presented much better stability under illumination than BHJ devices. Moreover, this simple PHJ-OSC fabrication method can be further extended to different acceptor systems to build efficient and stable OSCs.